2017
DOI: 10.1002/app.44779
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide (scCO2) dispersion of poly(ethylene terephthalate)/clay nanocomposites: Structural, mechanical, thermal, and barrier properties

Abstract: Dispersed poly(ethylene terephthalate) (PET)/clay nanocomposites can lead to materials with superior barrier and mechanical properties. PET/clay nanocomposites were prepared by melting extrusion of PET with as-received or supercritical carbon dioxide (scCO 2 ) predispersed Cloisite V R 30B (30B). The predispersion of 30B was assessed by WAXD, SEM, and TGA, and results indicated that scCO 2 processing could predisperse 30B and the surface modification of the clay was preserved after processing. The structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…RESULTS AND DISCUSSION Figure 1 shows the XRD patterns for PET/clay nanocomposites prepared with 5 wt% ScCO2 and without scCO2. These patterns similar to the previous studies results of Fengyuan Yang [14] FIG1: NC's with 5wt% clay (A) 30B (B) 20A and (C) 10B WAXD patterns All NC showed properly-described both d001 and d002 diffraction peaks, no matter their surface chemistry or processing of scCO2, advising the existence of sure exceeding clay structures which are ordered in all NC. In addition, all of NC confirmed shifts of the d001 peaks to especially lower 2θ compared with corresponding pristine clays, advising that the polymer have been embedded into the galleries of clay.…”
Section: IIIsupporting
confidence: 88%
See 3 more Smart Citations
“…RESULTS AND DISCUSSION Figure 1 shows the XRD patterns for PET/clay nanocomposites prepared with 5 wt% ScCO2 and without scCO2. These patterns similar to the previous studies results of Fengyuan Yang [14] FIG1: NC's with 5wt% clay (A) 30B (B) 20A and (C) 10B WAXD patterns All NC showed properly-described both d001 and d002 diffraction peaks, no matter their surface chemistry or processing of scCO2, advising the existence of sure exceeding clay structures which are ordered in all NC. In addition, all of NC confirmed shifts of the d001 peaks to especially lower 2θ compared with corresponding pristine clays, advising that the polymer have been embedded into the galleries of clay.…”
Section: IIIsupporting
confidence: 88%
“…Then resins of PET with diverse kinds of clay (scCO2 processed or as-received), modification (20A,30B and 10A) and fraction (1, 3 and five wt%) had been closed in a foil bag made of aluminium and blended mechanically by the usage of a "Thumler's tumbler" for 12h before extrusion. [14] PET/clay NC have been compounded with the aid of the use of a micro-compounder of laboratory scale ("Thermo Haake Minilab") with a recirculation channel which permits the processing of batches of usually 5-40 g, a barrel temperature of 265 o C and screws of twin counter-rotations at a velocity of 50rpm. At last, the strands which have been extruded cooled down to the temperature of the room and are made into pellets.…”
Section: A Materials Experimental Equipment and Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Young's modulus was improved up to 33% using 4 wt% 30B clay, whereas reduction in toughness was around 92%. Yang et al [17] reported supercritical carbon dioxide pre-dispersed Cloisite 30B melt extruded with PET matrix. The Young's modulus and tensile strength were improved by 12% and ~ 25%, respectively, whereas elongation at break was reduced by ~ 80%.…”
Section: Introductionmentioning
confidence: 99%